2022
DOI: 10.1371/journal.pone.0264159
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of anti-SARS-CoV-2 antibody diagnostic tests in Brazil

Abstract: Background Although serologic tests for COVID-19 diagnosis are rarely indicated nowadays, they remain commercially available and widely used in Brazil. The objective of this study was to evaluate the cost-effectiveness of anti-SARS-CoV-2antibody diagnostic tests for COVID-19 in Brazil. Methods Eleven commercially available diagnostic tests, comprising five lateral-flow immunochromatographic assays (LFAs) and six immunoenzymatic assays (ELISA) were analyzed from the perspective of the Brazilian Unified Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
7
0
3
Order By: Relevance
“…In Brazil, the Ministry of Health recommends the choice of RT-PCR and TR-Ag tests for symptomatic patients in the acute phase and that they be collected until the 8th day of symptoms. However, our study demonstrates that TR-Ag can be especially used in the initial phase of the disease for screening and diagnosis, especially in environments where there is a limitation in the laboratory processing capacity [ 14 , 27 , 36 ]. In addition, some studies have shown false results-negatives in significant amount in the first days of infection (0 to 7 days) for RT-PCR [ 8 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the Ministry of Health recommends the choice of RT-PCR and TR-Ag tests for symptomatic patients in the acute phase and that they be collected until the 8th day of symptoms. However, our study demonstrates that TR-Ag can be especially used in the initial phase of the disease for screening and diagnosis, especially in environments where there is a limitation in the laboratory processing capacity [ 14 , 27 , 36 ]. In addition, some studies have shown false results-negatives in significant amount in the first days of infection (0 to 7 days) for RT-PCR [ 8 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the notorious importance of detecting patients infected by SARS-CoV-2 for the control of the pandemic, there is a limited availability in the literature of economic analysis that guide the use of technology with the best cost-effectiveness ratio for this economic scenario [ 14 ]. Given the high availability of technologies and different brands available, decision-making by the public administration becomes complex [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed earlier in this review, rapid test kits for SARS-CoV-2 were not only cheaper but also easily accessible to the public, enabling instant testing and screening for the infection. This helped reduce the reliance on laboratory-based testing methods like RT-PCR, which, in addition to being laborious, incurred high costs in terms of personnel, machinery, and testing facilities [64]. Furthermore, cryptococcal antigen (CRAG)-LFA was used to screen for cryptococcal meningitis (CM) among HIV patients in Uganda.…”
Section: Cost-effectiveness Of Lfamentioning
confidence: 99%
“…Using data from the Brazilian public health system, de Assis et al [11] found that ELISA tests were more sensitive and cost-effective for high COVID-19 prevalence than LFIA, while LFIA had better specificity and was more costeffective for low COVID-19 prevalence. There are works focusing on developing more sensitive and accurate LFIA tests, with Guo et al [12] giving a good review.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [13] and Mohit et al [14] found significant variance in performance in papers studying different tests. de Assis et al [11] compared several ELISA and LFIA tests simultaneously with similar study and control groups. Their results are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%